Exploring Secondary Students' Behavioral Engangement Through Guessing Game in Vocabulary Classroom - Maulana, Irfan; Ahmad, Yousef Bani; Puspitaloka, Nina (Peneliti.net, 2024)
This study aims to explore students' behavioral engagement towards the use of guessing game technique in vocabulary learning. This is a qualitative research with case study as a research design. The participants were six grade 8 students in SPMN 1 Klari in Karawang who were categorized based on their low and high vocabulary learning. To obtain the desirable data, observation and interview guideline used for this research and then the obtained data analyzed through thematic analysis. The The findings showed that students had positive behavioral engagement in terms of their active participation in learning, their adherence to the rules, and their diverse emotions. It can be concluded that even a simple guessing game technique can help students in learning English vocabulary. owever, some problems such as boredom arise in learning.